2017
DOI: 10.18203/2319-2003.ijbcp20175694
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotics in schizophrenia: a retrospective study of drug utilization pattern in outpatient department of psychiatry at a tertiary care hospital

Abstract: Background: Psychiatric disorders are one of the major causes of morbidity and the burden of illness is enormous and remains grossly under represented. Psychotropic drugs have had a remarkable impact in psychiatric practice. Currently a large number of atypical antipsychotics available in the market are endorsed as better options for treating schizophrenia than the typical antipsychotics. The main objective of the study was to find the commonly prescribed antipsychotics in schizophrenia patients in a tertiary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
(14 reference statements)
0
8
0
2
Order By: Relevance
“…This was in contrast to the findings seen in study by Patted where only 47.3% patients received drugs from NLEM. 19 In this study 6.2% of injectables were prescribed. Depot preparation of fluphenazine decanoate was given in 3.7% of uncooperative patients.…”
Section: Discussionmentioning
confidence: 98%
“…This was in contrast to the findings seen in study by Patted where only 47.3% patients received drugs from NLEM. 19 In this study 6.2% of injectables were prescribed. Depot preparation of fluphenazine decanoate was given in 3.7% of uncooperative patients.…”
Section: Discussionmentioning
confidence: 98%
“…23,31 Present study findings are in line with Balaji R et al, who found 50% use of medicines from NLEM 2015 and also with Patted UH et al, who found only 47.33% of patients received antipsychotics which were in the National list of essential medicines (NLEM) 2015. 39,42 But Rode SB et al, and George A et al, have depicted a higher percentage (i.e. 81.36% and 96.77%) use of drugs prescribed from essential drug list (WHO and Indian).…”
Section: Discussionmentioning
confidence: 99%
“…It is indicating that the age is one of the factors where the choice of the drug depends especially in elderly patients. Studies conducted by Usharani H Patted et al, [13] showed that olanzapine was the most commonly prescribed atypical antipsychotic 48.6% followed by risperidone 45.8%. In the present study the common antipsychotics prescribed were olanzapine (43%) followed by Quetiapine (30%).…”
Section: Discussionmentioning
confidence: 99%